2022
DOI: 10.3389/fpsyg.2022.874356
|View full text |Cite
|
Sign up to set email alerts
|

Chinese English as a Foreign Language Teachers’ Immunity and Mindfulness as Predictors of Their Work Engagement

Abstract: Considering the significant contribution of teachers’ professional triumph in the prosperity of students, the current study aims to investigate the existence of any relationship among three factors influencing teachers’ success: immunity, mindfulness, and engagement. Furthermore, we attempt to investigate whether English as a foreign language (EFL) teachers’ immunity and mindfulness can predict their work engagement. To this end, a Likert-scale questionnaire including items on teacher immunity, mindfulness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Accordingly, the first null hypothesis stating that the English university teachers' CT does not predict their immunity was rejected. The contribution of higher order thinking skills to English teachers' immunity has been confirmed in the previous studies (e.g., Rahmati et al, 2019 ; Rahimpour et al, 2020 ; Atefi Boroujeni et al, 2021 ; Li, 2022 ). For instance, Rahimpour et al ( 2020 ) found that reflective teaching and language teachers' immunity were closely related.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Accordingly, the first null hypothesis stating that the English university teachers' CT does not predict their immunity was rejected. The contribution of higher order thinking skills to English teachers' immunity has been confirmed in the previous studies (e.g., Rahmati et al, 2019 ; Rahimpour et al, 2020 ; Atefi Boroujeni et al, 2021 ; Li, 2022 ). For instance, Rahimpour et al ( 2020 ) found that reflective teaching and language teachers' immunity were closely related.…”
Section: Discussionsupporting
confidence: 67%
“…Their findings reflected those higher levels of work engagement and L2 grit immune EFL teachers in the face of different challenges during their professional lives. In a recent study in China, Li ( 2022 ) concluded that the relationship between EFL teachers' immunity, mindfulness, and work engagement was significantly positive. This study also necessitates the use of training courses for language teachers to enhance EFL teachers' immunity development, mindfulness, and engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have also contended that mindfulness can be improved through interferences and exercises ( Kabat-Zinn, 2003 ; Baer and Lykins, 2011 ). Mindfulness changes the educational set inside a classroom by enabling thinking, developing significance, and taking advantage of education ( Li, 2022 ). In a wanted mindful class, the teachers help their students with rebuilding significance, thinking about the educational experience, and taking the most benefit of the educational cycle ( Wang et al, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%